2009
DOI: 10.1055/s-0028-1082064
|View full text |Cite
|
Sign up to set email alerts
|

Use of Statins for the Treatment of Spontaneous Intracerebral Hemorrhage: Results of a Pilot Study

Abstract: The use of statins during the acute phase of ICH could be associated with a better outcome. Further clinical trials are necessary to confirm a possible therapeutic effect and evaluate the toxicity of statins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…42,43 A pilot clinical study with rosuvastatin showed improved in-hospital mortality and National Institutes of Health stroke scale with further clinical trials planned. 44 Despite preclinical associations between statin use and mortality, and perihematomal edema, the Simvastatin for ICH Study, a phase 2, randomized, blinded, placebo-controlled, efficacy study evaluating treatment with 80 mg of simvastatin or placebo for 14 days on perihematomal edema was terminated because of poor recruitment. 45 Peroxisome proliferatoractivated receptor γ in microglia/macrophages has been found to promote hematoma absorption and protect other animal brain cells from ICH-induced damage.…”
Section: Pharmacological Manipulation Of Inflammation and Oxidative Smentioning
confidence: 99%
“…42,43 A pilot clinical study with rosuvastatin showed improved in-hospital mortality and National Institutes of Health stroke scale with further clinical trials planned. 44 Despite preclinical associations between statin use and mortality, and perihematomal edema, the Simvastatin for ICH Study, a phase 2, randomized, blinded, placebo-controlled, efficacy study evaluating treatment with 80 mg of simvastatin or placebo for 14 days on perihematomal edema was terminated because of poor recruitment. 45 Peroxisome proliferatoractivated receptor γ in microglia/macrophages has been found to promote hematoma absorption and protect other animal brain cells from ICH-induced damage.…”
Section: Pharmacological Manipulation Of Inflammation and Oxidative Smentioning
confidence: 99%
“…The same patient population also demonstrated an association between statin use prior to ICH and decreased absolute and relative perihematomal edema at presentation [132]. There is a report of 1 small, prospective cohort of 18 patients treated with rosuvastatin compared to 57 historical controls [133]. The mortality rate during hospitalization was 5.6% in the statin group and 15.8% in the control group with an adjusted hazard ratio of 0.20 (95% CI 0.02-1.67), also suggesting that the use of statins during the acute phase of ICH may be associated with improved mortality.…”
Section: Anti-inflammatory Agents: Statinsmentioning
confidence: 87%
“…Fourth, our study cannot apply to clinical human trial yet. Although the benefits or advantages of statins have been studied in clinical trials with several groups [22], the studies with deferoxamine have been only accepted in the experimental laboratory-even though clinically used for some diseases such as thalassemia major and sickle cell anemia-due to its toxic side effect including ocular problems, auditory abnormalities, pancytopenia, pulmonary complications and bone abnormalities [23].…”
Section: Discussionmentioning
confidence: 99%